COMMUNITY LANGUAGE LEARNING METHOD: ENHANCING SECONDARY SCHOOL STUDENTS’ ENGLISH VOCABULARY AT SMP NEGERI 4 KOTA TERNATE - Adi F. Mahmud (Universitas Sembilanbelas November Kolaka, 2016)
Vocabulary is a fundamental unit in learning a language. Vocabulary drives us in learning and understanding English skills (reading, listening, speaking, and writing). Without vocabulary, a reader, listener, speaker, or writer does nothing. This study attempted to carry out Community Language Learning Method to enhance secondary school students’ English vocabulary. Its hypotheses are (1) Community Language Learning Method cannot enhance secondary school students’ English vocabulary (H0) and (2) Community Language Learning Method enhance secondary school students’ English vocabulary (H1). This study used quantitative study by applying experimental design of one group pretest-posttest. The population was secondary school students at SMP Negri 4 Kota Ternate. The number of the population were 337 students. The sample was 35 students from the secondary school. They classified into two sexes namely; 15 male students and 20 female students. Simple random sampling technique used in taking the sample. The instrument applied in this study was a multiple choice test. It consisted of 30 items. The data were collected by applying pretest, treatment, and posttest. The data obtained were analyzed by using t-test formula from SPSS 16 version. Data findings and analysis on score mean and standard deviation indicated that pretest score mean was lower then posttest = (15.625), than for the posttest score mean was higher than pretest = (72.69). And, it compared standard deviation of pretest and posttest, standard deviation score of pretest and posttest showed difference each other. Standard deviation score of pretest = (15.625) and posttest = (10.707). it means that the independent variable had an effect on the total score of the subject (dependent variable). Moreover, t-test results showed that the average score in posttest x2 = 40.163. is greater than pretest x1 = 15.037. by applying the level of significance of 0.5. Therefore, its conclusion that the Community Language Learning Method is effective in teaching English vocabulary to the secondary school students. The alternative hypothesis stating that the Community Language Learning Method enhance students’ English vocabulary was accepted (H1)and null hypothesis stating that the Community Language Learning Method cannot enhance students’ English vocabulary was rejected (H0).